1972
DOI: 10.1021/ja00774a004
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of phenylcyclopropanes and phenylethanes. Unusual emissions from phenylcyclopropanes

Abstract: We have applied single determinant ab initio molecular orbital theory to the description of internal rotation in vinylcyclopropane and vinylcyclobutane. Using the minimal STO-3G basis we find the two molecules to be most stable in their s-trans forms but also predict both to possess flat secondary s-cis and gauche minima. Further investigation on vinylcyclopropane with the extended 4-31G basis set confirms the gauche minimum but places doubt on the stability of the s-cis structure. Substitution on the vinyl gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…The electronic absorption spectra of 1B were calculated by TD-DFT-B3LYP (-B97D) with 25 lowest singlet states. The calculated wavelengths of main UV-vis absorption peaks (simulated by B97D, about 277.58 and 217.88 nm) were only about 1 and 12 nm differences compared to the experimental results, [27,28] which demonstrated that B97D was a suitable method for cyclopropane derivatives. However, B3LYP overestimated the excitation energies.…”
Section: Theoretical Evidence and Computational Detailsmentioning
confidence: 72%
“…The electronic absorption spectra of 1B were calculated by TD-DFT-B3LYP (-B97D) with 25 lowest singlet states. The calculated wavelengths of main UV-vis absorption peaks (simulated by B97D, about 277.58 and 217.88 nm) were only about 1 and 12 nm differences compared to the experimental results, [27,28] which demonstrated that B97D was a suitable method for cyclopropane derivatives. However, B3LYP overestimated the excitation energies.…”
Section: Theoretical Evidence and Computational Detailsmentioning
confidence: 72%
“…Bibenzyl modes, on the other hand, experience little enhancement because the excited electronic states of bibenzyl are much higher in energy than those of DPOT. 38 From this series of 2/4 scans, the DPOT 1150 cm Ϫ1 resonance was referenced to the bibenzyl 1200 cm Ϫ1 resonance. The ratio of peak areas was measured in this case because the DPOT 1150 cm Ϫ1 line is broad ͑FWHMϷ6 cm Ϫ1 ͒ and no doubt comprises more than one resonance and perhaps overlapping sites.…”
Section: Site-selective Fluorescence and Fluorescence Excitation Specmentioning
confidence: 99%
“…Photoreactions of 1,2‐diphenylcyclopropanes ( 1 ), reported by Becker and Ramamurthy, also display “unusual” luminescence behavior associated with excited state biradical generation by photoinduced C–C bond cleavage (Scheme A) . Although many mechanistic studies of this photoreaction have been performed, the detailed mechanism still remains unclear.…”
Section: Introductionmentioning
confidence: 99%